2014
DOI: 10.35196/rfm.2014.3.209
|View full text |Cite
|
Sign up to set email alerts
|

LA DIVERSIDAD MORFOLÓGICA in situ DE CHILES SILVESTRES (Capsicum spp.) DE TABASCO, MÉXICO

Abstract: En el estado de Tabasco, México se pueden encontrar plantas de chile (Capsicum spp.) de forma silvestre que se diferencian por sus características morfológicas. Con el objetivo de recolectar y evaluar in situ la diversidad morfológica de chiles silvestres, de enero a septiembre de 2013 se realizó la exploración de 48 comunidades en 14 municipios del estado de Tabasco. Durante la exploración se recolectaron y tomaron datos de variables de planta, flor y fruto de 89 colectas. Se encontró la presencia de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
3
10
0
1
Order By: Relevance
“…PC1 explained 35.8% of total morphological variation, which was positively determined by the variables fruit shape, fruit shape at the juncture with the pedicel and fruit apex shape, and negatively by the variables fruit length and fruit weight. This indicates that the component was determined by fruit variables, which is consistent with previous studies on the morphological diversity of wild peppers, in which it was reported that the first component was explained by fruit variables (Narez-Jiménez et al, 2014). PC2 explained 17.1% of total morphological variability, with the variables stem diameter, plant height, plant width, leaf color, leaf length, leaf width, fruit length, fruit width and number of seeds per fruit being the variables that contributed most to the explanation of the component.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…PC1 explained 35.8% of total morphological variation, which was positively determined by the variables fruit shape, fruit shape at the juncture with the pedicel and fruit apex shape, and negatively by the variables fruit length and fruit weight. This indicates that the component was determined by fruit variables, which is consistent with previous studies on the morphological diversity of wild peppers, in which it was reported that the first component was explained by fruit variables (Narez-Jiménez et al, 2014). PC2 explained 17.1% of total morphological variability, with the variables stem diameter, plant height, plant width, leaf color, leaf length, leaf width, fruit length, fruit width and number of seeds per fruit being the variables that contributed most to the explanation of the component.…”
Section: Resultssupporting
confidence: 92%
“…The first group was formed by 71 collections that have fruits of lower weight, a round shape and a blunt or sunken apex, while the second group was formed by 60 collections, which are located in the negative quadrant of PC1 and are distributed in the positive and negative quadrant of PC2; this group was formed by collections that have fruits of greater weight, an elongated shape and a pointy fruit apex. In this regard, Castañón-Nájera et al (2008) and Narez-Jiménez et al (2014) report that the state of Tabasco has wild pepper morphotypes characterized by round and pointy fruits. In millimeters (mm) with a digital Vernier caliper graduated in mm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations